The New Mamlukes: Egyptian Society and Modern Feudalism by Amira El-Azhari Sonbol (Syracuse, NY: Syracuse University Press, 2000. 292 pages.) (American Journal of Islam and Society, 2002)
Amira El-Azhari Sonbol has written an outstanding socio-politico-economic analysis of the Egyptian government and society over the last threecenturies. This book brilliantly debunks the oriental despot model ofanalysis that has been imposed on scholarly studies of Muslim societies.She achieves this with the aid of a "study of popular discourse." Sheemphasizes the need to relearn what culture is all about by examining howEgyptians see themselves and their own relationships. She finds thatEgyptian society has not been static, waiting to be transformed from theoutside, but dynamic, following its own cultural evolution. Along the way,she notes the importance of distinguishing Islamic revival from radicalismand terrorism.Sonbol argues that eighteenth-century Egypt has been misunderstood,forced into the absolutist mold that more properly characterizes today'sEgypt. Eighteenth-century Egypt reflected "social maneuverability" andthe "rule of law." In the 19th and 20th centuries the Egyptian state sought,with partial success, to establish itself as the "active creator" of law andorder. A new form of mercantilism emerged that went beyond the mere controlof imports and exports to the manipulation of all aspects of productionand exchange to the benefit of the elites. In the Nasser era, elements ofsocialism and nationalism were employed in the advancement of what wasactually a form of state capitalism, in which the elites sought to extract rentfrom their hold on power. It was a feudal compact, in which the state's"right" to political allegiance was "reciprocated by the state's 'duty' toguarantee the security of the nation and provide its people with" the necessitiesof life.Sonbol critiques the translation of khassa as elite and 'ammah as generalpub I ic. The khassa are the people of power, wealth, and distinction, onlyone part of which retains hegemony at any given time. The khassa are toodiverse (ruling elites, the military, and the business classes) to be consideredan aristocracy. From time to time the ulema, the intellectuals and the professionals have been their allies in legitimizing their power. The so-calledmodernization of the Arab world has only been a strengthening of ...